A randomized, double-blind, single-dose study (LAVENDER) to assess the safety, tolerability, pharmacokinetics, and immunogenicity of a combined infusion of ABP 980 and pertuzumab in healthy subjects - Hanes, Vladimir; Chow, Vincent; Stewart, Tina; Puri, Adeep (Cancer chemotherapy and pharmacology, 2021)
Purpose ABP 980 (KANJINTI ™ ) is a biosimilar to reference product HERCEPTIN ® (trastuzumab RP). The goal of this study was to characterize the safety, tolerability, and immunogenicity of ABP 980 plus pertuzumab (PERJETA ® ) when co-administered in a single infusion bag in healthy subjects. Methods This randomized, double-blind, single-dose, 2-arm, parallel-group study (LAVENDER Study) evaluated an intravenous (IV) infusion of ABP 980 (6 mg/kg) plus pertuzumab (420 mg) combined in a single infusion bag relative to an IV infusion of trastuzumab RP (6 mg/kg) plus pertuzumab (420 mg) combined in a single infusion bag given over 60 min. The subjects were followed for 92 days post dosing. Results A total of 42 subjects were enrolled in the study and treated with investigational product. Due to an operational issue during dosing, the first 6 subjects enrolled in the study were replaced. A total of 36 randomized subjects, n = 18 for ABP 980 plus pertuzumab and n = 18 for trastuzumab RP plus pertuzumab, were treated. Resulting serum concentrations of ABP 980 and trastuzumab RP were similar. There were no serious adverse events, no deaths, and no cardiac disorders during the study. No subject developed anti-drug antibodies throughout the study. Conclusions This study demonstrated the safety and tolerability of ABP 980 and pertuzumab admixture in a single infusion bag. The safety profiles and pharmacokinetic parameters of ABP 980 and pertuzumab were consistent with what is known for trastuzumab RP and pertuzumab. Clinical trial listing EudraCT 2018-002903-33.